2013
DOI: 10.1371/journal.pone.0065009
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Repeated Thought Suppression Success

Abstract: Intrusive thoughts and attempts to suppress them are common, but while suppression may be effective in the short-term, it can increase thought recurrence in the long-term. Because intentional suppression involves controlled processing, and many aspects of controlled processing decline with age, age differences in thought suppression outcomes may emerge, especially over repeated thought suppression attempts as cognitive resources are expended. Using multilevel modeling, we examined age differences in reactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 52 publications
2
20
1
Order By: Relevance
“…In addition to the IAMI and the voluntary control questions, we also included the DDFS, WBSI, and the DES II (used in Study 2). We expected to replicate previous work showing an age related decline for daydreaming frequency (Giambra, 1989; 1993), thought suppression (Erskine et al, 2007; Lambert et al, 2013) and trait dissociation (e.g., Ross et al, 1990). However, we expected involuntary autobiographical memories (the past directed IAMI) to form an exception from this pattern, on the basis of work suggesting involuntary episodic remembering to be less cognitively demanding than voluntary episodic remembering (e.g., Hall et al, 2014; Berntsen, Staugaard, and Sørensen, 2013) and therefore less effected by a general cognitive decline in older adulthood.…”
Section: Studysupporting
confidence: 51%
See 2 more Smart Citations
“…In addition to the IAMI and the voluntary control questions, we also included the DDFS, WBSI, and the DES II (used in Study 2). We expected to replicate previous work showing an age related decline for daydreaming frequency (Giambra, 1989; 1993), thought suppression (Erskine et al, 2007; Lambert et al, 2013) and trait dissociation (e.g., Ross et al, 1990). However, we expected involuntary autobiographical memories (the past directed IAMI) to form an exception from this pattern, on the basis of work suggesting involuntary episodic remembering to be less cognitively demanding than voluntary episodic remembering (e.g., Hall et al, 2014; Berntsen, Staugaard, and Sørensen, 2013) and therefore less effected by a general cognitive decline in older adulthood.…”
Section: Studysupporting
confidence: 51%
“…One theoretically meaningful candidate might be the age of the individual. In addition to negative affect, previous research has demonstrated consistent negative associations between age and frequency of day dreaming (Giambra, 1989; 1993), thought suppression (Erskine, Kvavilashvili, & Kornbrot, 2007; Lambert, Smyth, Beadel & Teachman, 2013) and trait dissociation (e.g., Ross, Joshi & Currie, 1990). In contrast, we should not expect an age-related decline for the past dimension of the IAMI following the theoretical position that involuntary autobiographical memories form a basic mode of remembering that requires less executive processes and therefore may show less age-related impairments (Berntsen, 2009; 2012; Hall et al, 2014).…”
Section: Studymentioning
confidence: 95%
See 1 more Smart Citation
“…We believe that the current findings can partly explain both the frequently reported drop in the prevalence of anxiety and depression in older adults, but also the positivity effect often reported in older adults whereby they show rapid avoidance of negative and threatening information including memories (Carstensen, 2006;Schlagman et al, 2009). Furthermore, one recent study has shown that older adults may be more successful at thought suppression suffering less intrusions than younger adults (Lambert, Smyth, Beadel & Teachman, 2013). If individuals become more repressive with ageing this may explain the reduction in intrusive thoughts found by Lambert and colleagues (Lambert et al 2013).…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, one recent study has shown that older adults may be more successful at thought suppression suffering less intrusions than younger adults (Lambert, Smyth, Beadel & Teachman, 2013). If individuals become more repressive with ageing this may explain the reduction in intrusive thoughts found by Lambert and colleagues (Lambert et al 2013).…”
Section: Discussionmentioning
confidence: 96%